1985
DOI: 10.1042/cs0690051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bromocriptine Treatment on Prolactin, Noradrenaline and Blood Pressure in Hypertensive Haemodialysis Patients

Abstract: Bromocriptine (2.5 mg/day orally) produced a significant fall in supine mean arterial pressure in nine hypertensive haemodialysis patients with high serum prolactin levels, without causing significant changes in heart rate. On bromocriptine, there was a significant decrease in the mean value of both serum prolactin and plasma noradrenaline, without significant changes in the mean value of plasma renin activity. A significant relationship was found between the changes in supine plasma noradrenaline and the chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…However, it is unknown whether prolactin normalization improved any atherosclerotic/ cardiovascular-related outcomes. Intriguingly, some small studies have evaluated the effects of bromocriptine therapy in CKD patients on the basis of its dopamine D2 receptor agonist properties, reporting a reduction in BP and regression of left ventricular hypertrophy in dialysis patients (41)(42)(43). Whether this effect was mediated by prolactin reduction, at least partly, is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown whether prolactin normalization improved any atherosclerotic/ cardiovascular-related outcomes. Intriguingly, some small studies have evaluated the effects of bromocriptine therapy in CKD patients on the basis of its dopamine D2 receptor agonist properties, reporting a reduction in BP and regression of left ventricular hypertrophy in dialysis patients (41)(42)(43). Whether this effect was mediated by prolactin reduction, at least partly, is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Bromocriptine‐QR (B‐QR), a quick‐release formulation of micronized bromocriptine, is the only sympatholytic dopamine‐agonist US FDA‐approved for the treatment of type 2 diabetes. In several preclinical and clinical studies, bromocriptine administration has repeatedly been demonstrated to reduce measures of elevated SNS activity such as reduction of elevated sympathetic outflow, plasma norepinephrine, BP and/or conversion of nondipper profile of circadian mean arterial pressure to a dipper profile. A critical aspect of dopaminergic control of autonomic function is via circadian modulation of the central biological clock pacemaker circuit (circadian neuronal afferent signals to and including the suprachiasmatic nuclei [SCN]) (see below).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PRL levels decreased significantly as compared with the PBO group, suggesting an improvement in the dopaminergic tone. A cardioprotective effect of BEC, expressed as a reduction in blood pressure, has been previously reported in hypertensive patients with end-stage renal disease (ESRD) on peritoneal dialysis or hemodialysis [17, 21–23]. More recent reports suggest that the elevated levels of NE and the sympathetic overactivity stimulate and promote cardiomyocyte hypertrophy and myocardial fibrosis resulting in increased LV mass [19, 20, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Bromocriptine (BEC; bromoergocriptine), a type-2 dopamine receptor (D2) agonist, can reduce sympathetic activity and levels of circulating NE and thus contribute to the management of high blood pressure and LVH in patients with CKD. In previous studies, it has been demonstrated that the use of low doses of BEC permits adequate blood pressure control and reduces LV mass in both peritoneal dialysis and hemodialysis patients [21–23]. …”
Section: Introductionmentioning
confidence: 99%